RESTRICTION FACTORS TO IMPLEMENT SAFETY PRACTICES IN SMALL GRADE CONTRACTORS - Noorhayatie, Yusof; Mohd Saidin, Misnan (UTM Press, 2019)
This study was focused on small grade contractor in Malaysian construction industry. The total of small grade contractors in Malaysia registered by Construction Industry Development Board (CIDB) is higher and increases for every year. However, it is well known that construction project are exposed to accidents and injuries including of minor accidents, ergonomics problems, out dated machinery can cause the machine breakdown, and lack of awareness from employers and employees. The statistic of construction accidents is one of the critical sectors that need a huge and fast overhaul from the current site safety practices. Moreover, the safety practice in small grade contractors is too far to achieve the good safety performance in construction industry compare to large grade contractors. In this study, a semi-structured question was developed to identify the factors that affecting safety practice in small grade contractors. The data used in this study was collected through the interview with manager in small grade contractors, Site Safety Supervisor (SSS), and Safety and Health Officer (SHO). The finding of this paper was identified factors that influence safety practice in small grade contractors such as poor Occupational Safety and Health (OSH) management; small project value; financial constraint; lack of training and knowledge on safety management; high competition; lack of communication; unsatisfactory safety motivation; not exposed with good safety culture on site; the existing OSH framework is fragmented; difficult in contract acquirement; do not have SSS, SHO or safety person in charge; lack of OSH formal documentation; financial limitation and time constraints. The critical factors lack of safety practice which are financial limitation and lack of training and knowledge. In conclusion, small grade contractors faced for some factors that avoid them to implement safety practice in their companies.